HUBUNGAN KEMAMPUAN DAN MOTIVASI KERJA DENGAN PRESTASI KERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RUMAH SAKIT CAMATHA SAHIDYA KOTA BATAM TAHUN 2021 - Cevy Amelia; Sarmini Sarmini (Ensiklopedia of Journal, 2022)
Work performance is related to the ability to work and motivation in carrying out work. Based on the presurvey, it was obtained interviews from 11 nurses who said that some of them had participated in research that supported their work and were motivated because they had just finished their education, but some nurses were less motivated because they felt that the reward had not been noticed and did not know what the work assessment was like. The purpose of this research is to know the relationship between ability and work motivation with a cross-sectional approach. The population in this study were all nurses in the inpatient room totaling 52 people. Sampling using total sampling. The research site was at Camatha Sahidya Hospital, Batam City on June 24 – August 12. Collecting data using a questionnaire adopted from Wahyudi (2010) regarding ability while a questionnaire about motivation and achievement was adopted from Adryani (2012). This study used univariate (frequency distribution) and bivariate (chi-square) analysis. The results obtained that more than half of the implementing nurses have the ability in the high category and more than half with the low category on work motivation and work performance. Furthermore, there is a relationship between ability and work performance (p Value 0.000) and there is a relationship between work motivation and work performance (p Value 0.009). Based on the conclusions of the researchers, it is recommended for hospital management to continue to maintain and improve the work motivation of implementing nurses and complete the supporting needs in improving nursing services, work motivation of nurses in carrying out their duties by creating a system of rewards that provide feedback on the performance that has been carried out by nurses.Keywords: Ability, Work Motivation, Work Performance